Representative of Self Care Management of DMT2 Sufferers in the Working Area of Primary Health Facilities in Mojokerto City - Eka Nur Soemah; Della Puspita Anggraini; Agus Haryanto (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Type 2 Diabetes Mellitus (DMT2) requires effective self-care management to prevent complications. The health center in Mojokerto City plays a crucial role as the front line in education and support for DMT2 sufferers. This study aims to identify the level of self-care management in DMT2 patients in the work area of the First Level Health Facility (FKTP) of Mojokerto City. This descriptive study involved 372 respondents selected using the Slovin formula (5% error tolerance) from a population of 5,328 DMT2 sufferers. The instrument used is the Diabetes Self-Management Questionnaire (DSMQ). The distribution of the level of self-care management shows an almost even distribution: the Low category is 33.87% (126 people), the High category is 33.33% (124 people), and the Medium category is 32.80% (122 people). The high proportion of the low category (33.87%) indicates that good access to information has not been fully able to improve patient compliance and independent practices. This shows that there are practical obstacles or motivations in the application of medical information. Self-efficacy is a key factor; the higher the patient's self-confidence, the better the self-care management practices are performed. A more applicable educational strategy and strengthening psychological support are needed to increase the independence of DMT2 sufferers in Mojokerto City.